Decolorization of Synthetic Dyes by Laccase of Phellinus noxius BRB 11 Immobilized with Halloysite Nanotubes - Naser, Inda Hastuti N; Kemala, Tetty; Yanto, Dede Heri Yuli; Purwaningsih, Henny; Nurhayat, Oktan Dwi; Ardiati, Fenny Clara; Bakar, N.H.H Abu; Iqbal, Anwar (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
Halloysite nanotubes (HNTs) have been proposed as promising supports for enzyme immobilization. Developing an effective technique for enzyme immobilization on HNTs is crucial for their practical application. In this study, we present a method for immobilizing laccase enzymes on HNTs using various amino acids as green cross-linkers for eco-friendly decolorization of synthetic dye. The modified HNTs were characterized using FT-IR, FE-SEM, and HR-TEM analyses. Furthermore, the effects of various parameters—including pH (ranging from 3 to 8), temperature (30-70°C), toxicity, and reusability—on the activity of both free and immobilized laccase were investigated. The results indicated that glycine (Gly) provided the most effective support for laccase immobilization on HNTs. The modified HNTs/Gly-Lac achieved an immobilization yield of 98.45% and successfully decolorized 94.60% of Acid Blue 129 (AB129) within 2 h. The successful immobilization of laccase onto functionalized HNTs was confirmed through FT-IR, FE-SEM, and HR-TEM analyses. Morphological observations of HNTs/Gly for laccase immobilization showed a thickened and roughened appearance with a thin, light gray layer on the outer surface. Additionally, the presence of an imine (-C=N-) bond peak and a peak at 1410 cm-1, corresponding to the (-NH) bond, suggested successful covalent immobilization. The toxicity analysis revealed a reduction in the toxicity of laccase after immobilization onto modified HNTs. A reusability assessment conducted over five cycles demonstrated that decolorization efficiency remained above 45%. These findings suggest that HNTs/GlyLac could serve as an effective material for textile dye wastewater treatment.